Tacrolimus Toxicity due to Biliary Obstruction in a Combined Kidney and Liver Transplant Recipient - Samuel Chan; Michael T. Burke; David W. Johnson; Ross S. Francis; David W. Mudge (Case Reports in Transplantation)
The immunosuppressant tacrolimus has a narrow therapeutic window, necessitating therapeutic drug monitoring to maintain efficacy and minimise toxicity. There are very few reports examining the impact of impaired biliary excretion on tacrolimus blood levels or toxicity. We report the case of a 26-year-old combined liver and kidney transplant recipient, who developed acute biliary obstruction leading to tacrolimus toxicity with very high blood tacrolimus levels. Despite a careful evaluation, no alternative cause was found for her acute kidney injury, and her kidney function returned to previous baseline within several days following treatment of the biliary obstruction and temporary withdrawal of tacrolimus.